Changes in Paleovegetation and Climate Seasonality in Central China Over Last Two Glacial Cycles: A Stable Isotope Perspective From Land Snails. Issue 10 (23rd October 2021) - Qin, Ben; Wu, Yan; Cui, Linlin; Wu, Naiqin; Du, Shuisheng; Wang, Xu; Ding, Zhongli
Abstract: Modern investigations have shown that oxygen and carbon isotopes of land snail shells are useful indicators of climate and vegetation in monsoonal regions. However, stable isotope studies on snail fossil shells have seldom been done, and the reliability of those indicators needs further verification. Moreover, intrashell stable isotope analysis of individual snails is rather scarce, and seasonal variation in the glacial‐interglacial monsoonal climate remains unclear. Therefore, we performed δ 18 O and δ 13 C analyses on fossil shells of cold‐aridiphilous Cathaica pulveratrix and subhumidiphilous Metodontia yantaiensis from the loess section over the last two glacial cycles at the Beiyao site on the southern Chinese Loess Plateau. The δ 18 O values of fossil shells reflected monsoonal rainfall amounts and more rainfall during MIS3 and MIS7 than during MIS4 and MIS6. Meanwhile, the δ 13 C values of fossil shells indicated the relative abundance of C3 /C4 plants and more C4 biomass during MIS3 and MIS7 than during MIS4 and MIS6. The δ 18 O and δ 13 C values of the two species from the same horizon are significantly different, reflecting differences in their growing season and/or physiological habits. Intrashell variations in stable isotopes showed that climatic seasonality was much stronger during the glacial periods than during the interglacials. Our findings provide an environmental background for explaining past human activities at the Beiyao site. The investigation of stone artifacts showed that ancient human activities were relatively strong during MIS3 and MIS7. During these stages, the warm and humid climate with smaller seasonal contrast was favorable for the regional expansion of human activities. Key Points: δ 18 O and δ 13 C values of C. pulveratrix and M. yantaiensis snails over the last 200 ka were studied to trace climate and vegetation changes δ 18 O values showed less rainfall and an approximately 1.5 times stronger seasonality during MIS4 and MIS6 than during MIS3 and MIS7 δ 13 C values revealed more C4 biomass during the warm/humid MIS3 and MIS7 stages and M. yantaiensis ingested more C4 than C. pulveratrix